2012
DOI: 10.1038/hr.2011.232
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates coupling factor 6-induced salt-sensitive hypertension and cardiac systolic dysfunction in mice

Abstract: In male coupling factor 6 (CF6)-overexpressing transgenic (TG) mice, a high-salt diet induces hypertension and cardiac systolic dysfunction with excessive reactive oxygen species generation. However, the role of gender in CF6-mediated pathophysiology is unknown. We investigated the effects of ovariectomy and estrogen replacement on hypertension, cardiac dysfunction and Rac1 activity, which activates radical generation and the mineralocorticoid receptor, in female TG mice. Fifteen-week-old male and female TG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…CF6 increases arterial blood pressure in rats, which is consistent with the high levels of CF6 seen in the plasma of patients diagnosed with hypertension [2]. CF6 functions are believed to be mediated by CF6 binding to the plasma membrane-bound ATP synthase, ecto-F1F0 complex, resulting in proton import and acidosis, whichin turn increases activated Rac1, a member of the Rho family of GTPases [3]. CF6 has several functions: it acts as a pro-atherogenic molecule in the cardiovascular system [4], regulated by estrogen in saltsensitive hypertension and cardiac systolic dysfunction in mice [3]; it attenuates exercise-induced physiological cardiac hypertrophy by inhibiting PI3K/Akt signaling in mice [5]; it plays a crucial role in the development of insulin resistance and hypertension [6]; and it appears to be a novel molecule for the pathogenesis and treatment of stroke [7].…”
supporting
confidence: 51%
See 1 more Smart Citation
“…CF6 increases arterial blood pressure in rats, which is consistent with the high levels of CF6 seen in the plasma of patients diagnosed with hypertension [2]. CF6 functions are believed to be mediated by CF6 binding to the plasma membrane-bound ATP synthase, ecto-F1F0 complex, resulting in proton import and acidosis, whichin turn increases activated Rac1, a member of the Rho family of GTPases [3]. CF6 has several functions: it acts as a pro-atherogenic molecule in the cardiovascular system [4], regulated by estrogen in saltsensitive hypertension and cardiac systolic dysfunction in mice [3]; it attenuates exercise-induced physiological cardiac hypertrophy by inhibiting PI3K/Akt signaling in mice [5]; it plays a crucial role in the development of insulin resistance and hypertension [6]; and it appears to be a novel molecule for the pathogenesis and treatment of stroke [7].…”
supporting
confidence: 51%
“…CF6 functions are believed to be mediated by CF6 binding to the plasma membrane-bound ATP synthase, ecto-F1F0 complex, resulting in proton import and acidosis, whichin turn increases activated Rac1, a member of the Rho family of GTPases [3]. CF6 has several functions: it acts as a pro-atherogenic molecule in the cardiovascular system [4], regulated by estrogen in saltsensitive hypertension and cardiac systolic dysfunction in mice [3]; it attenuates exercise-induced physiological cardiac hypertrophy by inhibiting PI3K/Akt signaling in mice [5]; it plays a crucial role in the development of insulin resistance and hypertension [6]; and it appears to be a novel molecule for the pathogenesis and treatment of stroke [7]. Studies have shown an elevated plasma level of CF6 in patients with essential hypertension, diabetes mellitus, end-stage renal disease, acute myocardial infarction, and coronary heart disease [8]; however, research on CF6 in spontaneously hypertensive rats (SHRs) is mainly in vascular smooth muscle cells (VSMCs) and vascular endothelial cells [9,10].…”
mentioning
confidence: 99%
“…Each value was the average of at least three consecutive measurements [22]. Prior to sacrifice of the animals, RV systolic pressure (RVSP) was transduced from the right jugular vein into the vena cava and then into the right atrium followed by the right ventricle using a 1.4 F Millar Mikro-Tip catheter transducer (Millar Instruments Inc., Houston, TX).…”
Section: Methodsmentioning
confidence: 99%
“…2 In this issue of Hypertension Research , Izumiyama et al . 3 show that estrogen replacement has a cardioprotective function in ovariectomized females under a high-salt diet (HSD). Furthermore, they report on the mechanism whereby coupling factor 6 (CF6) overexpression increases salt-sensitive hypertension, resulting in enhanced cardiac systolic dysfunction.…”
mentioning
confidence: 99%
“…3 CF6 is a component of the intrinsic membrane domain (F0) of ATP synthase, which is considered to be essential for energy transduction. 12 Recently CF6 has been identified to have multiple extracellular roles as a circulating hormone.…”
mentioning
confidence: 99%